Co-Evolution of Standards in Innovation Systems The Dynamics of Voluntary and Legal Building Codes - Grs̲ser, Stefan N. (Contributions to Management Science,, 2013)
Mitigating climate change is one of the most profound challenges facing humankind. In industrialized countries, the residential housing sector produces roughly one-fourth of the greenhouse gas emissions. One solution to reduce these emissions is the availability of building codes that require high levels of energy efficiency. Given the current scientific knowledge, more research is needed to gain a proper systemic understanding of the underlying socio-economic and technical system. Such an understanding is crucial for developing high energy-efficiency standards because this system develops gradually over time and cannot be changed swiftly. This book creates a feedback-rich simulation model for analyzing the effects of different administrative policies on energy demand, the improvement of energy efficiency by means of building codes, and reductions in the greenhouse gas emissions. The dynamic model can contribute substantially to the discourse on energy policies and guide effective administrative interventions. The book will be a valuable resource for officials in the public energy administration, as well as researchers in the areas of innovation, diffusion processes, co-evolution, standardization, and simulation modelling.